2021
DOI: 10.1016/j.heliyon.2020.e05688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of anaplasmosis in small ruminants along a human-livestock-wildlife interface in Uganda

Abstract: Background: Information as regards the epidemiology of the Anaplasmataceae in small ruminants in several lowand middle-income countries is scarce. Methods: In this study a total of 712 DNA samples collected from small ruminants were analyzed for Anaplasmataceae and Anaplasma ovis using the 16S rRNA and MSP4 genes respectively. Infection risk was assessed by location, sex and age of the animals and qGIS® was used to construct spatial maps. Results: The prevalence of Anaplasmataceae spp was 89.1% (95% CI: 77.5-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
5
2
Order By: Relevance
“…Turning to consider the factors that contained no significant differences, such as the "barn-types" or "farming areas", most of the goat farmers in Chonburi province release their goats onto the ground, pasture, or nearby areas in order to make it easier for them to clean the stalls, together with letting goats to roam freely in order to reduce stress and decrease the amount of feed/water that farmers have to provide in the stalls. Particularly, result of 'the farming areas' in our study contradicted the study of Kasozi et al (2021) that small ruminants located at the forest edge (<0.3 km) showed higher prevalence of A. ovis infection than those found inland or midland regions associated with increased agricultural activity. Additionally, the samples of goats being raised in platformed-barns at all times should be included in further study.…”
Section: Discussioncontrasting
confidence: 99%
“…Turning to consider the factors that contained no significant differences, such as the "barn-types" or "farming areas", most of the goat farmers in Chonburi province release their goats onto the ground, pasture, or nearby areas in order to make it easier for them to clean the stalls, together with letting goats to roam freely in order to reduce stress and decrease the amount of feed/water that farmers have to provide in the stalls. Particularly, result of 'the farming areas' in our study contradicted the study of Kasozi et al (2021) that small ruminants located at the forest edge (<0.3 km) showed higher prevalence of A. ovis infection than those found inland or midland regions associated with increased agricultural activity. Additionally, the samples of goats being raised in platformed-barns at all times should be included in further study.…”
Section: Discussioncontrasting
confidence: 99%
“…The percentage of anaplasmosis in our study for sheep is 67% and for goat is 65% which is similar with that of the evaluations of (Dahmani et al, 2017) who also reported 69.7% prevalence in Nigeria similarly (Lee et al, 2018) reported 83.8% in Sudan and 89.1% in Uganda (Kasozi et al, 2021). in our results slightly a bit higher (67%) of anaplasmosis recorded in sheep as compared to goat (65%) which agree with the earlier studies recorded higher prevalence in Sheep compared with goats (Kasozi et al, 2021;Lee et al, 2018;Aouadi et al, 2017). Our results also not agree with the results of (Eisawi et al, 2020) who recorded higher prevalence of anaplasmosis in goats as compared to sheep in Sudan.…”
Section: Season Wise Prevalence Of Heamoprotozoans In Goatssupporting
confidence: 91%
“…There have been reports of A. ovis infections in sheep and goats across Africa, Europe, Asia and North America (Yin and Luo 2007;Han et al 2017). Finding A. ovis in sheep can be compared to studies in Sudan (Lee et al 2018), Tunisia (Said et al 2015, Senegal (Dahmani et al 2019), West Iran (Mohammadian, Noaman, and Emami 2021), and Uganda (Kasozi et al 2021) which recorded a higher prevalence of infections. The variations in A. ovis prevalence may be caused by stress factors such as coinfection and a dry and hot climate (Renneker et al 2013).…”
Section: Discussionmentioning
confidence: 99%